Dielectric and spin relaxation behaviour in DyFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Maity, Tuhin; Poddar, Pankaj (Journal of Applied Physics, 2011)
We report the temperature and frequency dependent dielectric measurements and ac magnetic susceptibility of chemically synthesized DyFeO3 nanoparticles (size similar to 50-60 nm). The measurement of the dielectric properties was carried out in a broad temperature (20-325 K) and frequency (1-10(6) Hz) range. The non-Debye type dipolar relaxation phenomenon was observed in the DyFeO3 nanoparticles, as confirmed by the Cole-Cole plots. The higher values of epsilon' at the lower frequencies are explained on the basis of the Maxwell-Wagner model. The Cole-Cole analysis enabled us to separate the contribution of relaxation times, resistance and capacitance in grain and grain boundaries in DyFeO3 nanocrystals. We found that with increasing temperature, the contribution of grain boundary resistance increases in comparison to the grain resistance. We also performed spin relaxation studies in a broad temperature and frequency range. Both the in-phase (chi') and out-of-phase (chi `') components of the ac magnetic susceptibilities of the DyFeO3 nanoparticles show a clear evidence at spin reorientation transition around 70K and T-N (Dy) around 4K as reported by us in our earlier study using the dc magnetic behaviour. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3669154]